The Placement Activity on the Canadian Employment Agency - Magun, Sunder (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
This paper studies three aspects of the job matching process of the Canada Employment Centres.